Manajemen Kesiapan Rekam Medis Elektronik Di Rumah Sakit TK III DR. R. Soeharsono Banjarmasin - Noor, Fatmawati Bakri; Yunita, Nirma; Ningsih, Eka Rahma (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
Health facilities are currently required to implement electronic medical records. Minister of Health Regulation Number 24 of 2022 concerning medical records. Every health service facility is required to implement electronic medical records. Therefore, readiness is needed to see the success of implementing RME in hospitals, which is currently still in the process of including forms available at the hospital into SIMRS to be applied. This study aims to determine the readiness of electronic medical records at the TK III Dr.R.Soeharsono Banjarmasin Hospital. This research method uses qualitative research with a descriptive research design. This research instrument uses interview and observation guidelines. The research subjects were the head of medical records, IT officer, inpatient registration officer and outpatient registration officer. The results of this research are that readiness in terms of quantity is adequate and in terms of quality is not yet adequate, readiness in terms of methods, there are no standard operating procedures, readiness in materials, there are no facilities, hardware is not ready and software is not ready, readiness of materials in manual medical records is currently it is still in use and will be transferred in stages, while the electricity or generator and computer network are not yet ready because there are still frequent problems with power outages and network disruptions. Based on the research results, it can be concluded that the readiness to implement electronic medical records at TK III Dr Hospital. R. Soeharsono Banjarmasin is not yet fully ready.